Stabilisation and remediation of heavy metals in mine tailings using Vetiveria zizanioides (L.) nash amended with iron-coated and uncoated rice husk ash - Sadiq, Tariq Faruq (2016)
Mine tailings are regarded as a major source of environmental pollution due to the presence of high concentration of heavy metals, which can cause various health hazards. Decontamination of the mine tailings is necessary to reduce the concentration and the bioavailability of heavy metals. In recent years, phytoremediation technique has gained increasing attention for extraction and/or stabilisation of heavy metals from solid substrate such as mine tailings since the technique is efficient, simple, cost-effective and environmentally friendly. This study was undertaken to evaluate the potential of rice husk ash (RHA) or iron coated rice husk ash (Fe-RHA) as amendments for stabilisation and remediation of heavy metals in Penjom gold mine tailings using vetiver grass (Vetiveria zizanioides (L.) Nash). At the beginning of the study, the physicochemical properties of mine tailing and RH ashes were analysed. The metals in the tailings were extracted using a microwave-digestion method and analyzed using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). Fourier Transformed Infrared Spectroscopy (FTIR), multipoint Brunauer-Emmett-Teller (BET) and Scanning Electron Microscope-Electron Dispersive Spectroscopy (SEM-EDS) were used for the characterisation of (RHA) or (Fe-RHA). In this study, a series of experiments were conducted under laboratory and glasshouse conditions. The first study was conducted to determine the effects of RHA and Fe-RHA on the distribution of heavy metals fractions in the mine tailings. In the second study, an experiment was carried out to determine the effects of different rates of RHA and Fe-RHA on heavy metals availability and mobility in mine tailings. The third study was conducted in a glass house to evaluate the ability of vetiver grass to phytoremediate heavy metals in mine tailings amended with either RHA or Fe-RHA. In the fourth study, the effects of nitrogen, phosphorus and potassium (NPK) fertiliser on phytoremediation were determined. In the final study, a pot experiment was conducted to determine the role of dissolved organic carbon (DOC) on the heavy metals availability and uptake by vetiver grass. For the first 3 studies the tailings were treated with 0, 5, 10 or 20% (w/w) of either RHA or Fe-RHA. For the 4th experiment tailings were amended with 10% (w/w) of either RHA or Fe-RHA and three rates (0, 50 and 100 kg ha-1) of NPK fertiliser. For the last experiment, the tailings amended with 10% (w/w) of RHA, Fe-RHA and W-RHA and 50 kg ha-1 of NPK fertiliser. The physicochemical analysis data show that the Penjom gold mine tailings had a slightly alkaline pH (7.90) and the texture was silty loam. In addition, the mine tailings contained a significant amount As (1625.25 mg kg−1), Cd (57.00 mg kg−1), Cr (31.44 mg kg−1), Cu (75.60 mg kg−1), Mn (790.03 mg kg−1), Pb (81.80 mg kg−1) and Zn (174.80 mg kg−1). The results also show increasing total surface area, pore surface area, pore volume and pore radius of Fe-RHA and W-RHA when compared to the RHA. The higher proportion of meso- and macropores than the micropores can be observed in all three ashes RHA, Fe-RHA and W-RHA SEM micrographs. Sequential extraction results show that addition of RHA and Fe-RHA significantly (P≤0.05) increased the easily exchangeable fraction and reduced carbonate and organic bound fraction of As. However the effects were the opposites for cationic metals. Both RHA and Fe-RHA applications reduced the easily exchangeable fraction and increased carbonate and organic bound fraction of Cd, Cr, Cu, Mn, Pb and Zn. In general, in the second study CaCl2-extractable Cr, Cu, Pb and Zn were not detected in both control and amended samples, probably due to their low bioavailability and mobility. In the untreated mine tailings, there was a significant (P≤0.05) increase in the extractable and mobility of As, Cd and Mn from the tailings with incubation time. On other hand, the addition of RHA or Fe-RHA at all rates significantly (P≤0.05) increased the CaCl2-extractable As and its mobility, compared to the controls over the incubation time. In contrast, the application of RHA and Fe-RHA reduced CaCl2-extractable and mobility of Cd and Mn. The addition of RHA and Fe-RHA had significant (P≤0.05) effects on the chemical properties of the tailings, total dry biomass and heavy metals uptake. Moreover, the results were dependent on the type of ash used and heavy metals. The application of RHA significantly (P≤0.05) increased the pH, whereas Fe-RHA addition decreased the pH of the tailings. Vetiver grass grown in all Fe-RHA and RHA amended tailings had lower root, shoot and total biomass production compared with the vetiver grass grown in the controls. There was a significant difference (P≤0.05) in total metals among vetiver grass grown under different types and rates of ashes. For example, the uptake of As was significantly increased at all application rates of RHA or Fe-RHA, while the uptake of cationic metals was decreased as the result of RHA and Fe-RHA application. Biological accumulation coefficient (BAC), biological transfer coefficient (BTC) and bioconcentration factor (BCF) of vetiver grass were significantly affected by the types and rates of ashes used. The BAC and BCF values of the vetiver grass for As and Zn increased with RHA application rate but the BTC values of As and Zn were decreased. In Fe-RHA amended samples, As concentration in the shoot, and root concentrations of Cd and Zn were significantly higher compared to the control. The Fe-RHA treated samples also had lower BAC and BTC values for As and Zn than the control. However, the BCF values for those elements were higher than the control. This observation is in good agreement with the results obtained from the fractionation and incubation studies. In addition, the results show that NPK fertiliser application to the tailings amended with RHA or Fe-RHA enhanced phytoremediation of metals. The addition of NPK fertiliser to the unamended tailings (controls) increased vetiver root, shoot and total dry biomass production. In contrast, application NPK fertiliser to RHA treated samples reduced the root, shoot and total plant biomass production. Additionally, there were no significantly (P>0.05) changes in roots, shoots and total dry biomass of vetiver grass due to increase NPK fertiliser to tailings amended with Fe-RHA. Addition NPK fertiliser to un-amended tailings reduced As uptake by vetiver grass but increased the uptakes of Cr, Mn and Zn. In NPK plus RHA amended samples, the plant uptakes of As, Zn, Cd, Cu and Zn were increased. In addition, In Fe-RHA amended samples plus NPK fertiliser the total plant uptake of As and Zn increased but Cr and Cu reduced It was observed that the DOC could be one of the reasons for increasing As uptake in vetiver grass grown in tailings amended with RHA. The uptake of As, Cd, Cu and Mn in samples without DOC, i.e. the W-RHA treated samples, was significantly (P≤0.05) reduced by 30, 1.2, 8 and 5 %, respectively, compared to their uptakes in RHA treated samples. It can be concluded from this study that vetiver grass had tolerance to high concentrations of heavy metals. Overall, the results suggest that phytoremediation process using vetiver grass was effective for remediation of heavy metals in mine tailings. Therefore, RHA and Fe-RHA can be used as amendments to reduce the toxicity of cationic elements in highly contaminated tailings or they can also be used to enhance the uptake of As by plants.